Decission of treatment with Iodine-131 of one patient previously irradiated with radiotherapy. (September 2016) - Jimenez, Jose Miguel; Garcia, Rocio; Seguro, Alvaro; Ruiz, Gema
Abstract : Introduction: With the purpose of starting a treatment with Iodine-131 it's necessary to evaluate the remanent organ doses of previous treatments with other radioactive sources. Purpose: To make sure that a new treatment with radiation will not increase the dose above a threshold value that could result in a deterministic effect. Materials and methods: Once diagnosed the hyperthyrodism in a patient of our hospital, the evaluation of the treatment with Iodine-131 should be evaluated analyzing other factors in addition to the pathology, uptake rate and hormonal indicators. The patient was irradiated eight years ago on the right mandibular region in the treatment of a LNH (Lymphoma No Hodgdkin). To evaluate the glandular doses that can uptake high radiation doses in the treatment with the Iodine-131, it's necessary to calculate the remanent dose, especially in salivary glands. For that purpose it's recovered the plan of the radiotherapy treatment. Results: In this case the remanent dose in salivary glands calculated biologically after eight years and added to the average doses with Iodine-131 doesn't overcome threshold values. Nevertheless in some publications are indicated maximum doses in salivary glands that should be taken into account when previous treatments with radiation have been made. Conclusion: With the treatment with Iodine-131 in patients previosly irradiated, the salivary glands should be considered to prevent some effects as the xerostomy. It's essential to promote after the administration of Iodine-131 some rules not to uptake the radiopharmaceuticals in some critical organs as the salivary glands.